Lessons/An AutobiographyLessons/An Autobiography, by WangAnDr. with LindenEugene. Reading, MA: Addison-Wesley. 1986, 248 pp., $17.95, cloth. - Greenfeld, Sue (Academy of Management Review, 1987)
The article reviews the book ?Lessons:An Autobiography,? by An Wang and Eugene Linden.